2018
DOI: 10.1111/ecoj.12469
|View full text |Cite
|
Sign up to set email alerts
|

The Openness‐equality Trade‐off in Global Redistribution

Abstract: The Gulf Cooperation Council (GCC) countries accept massive numbers of migrants from poor countries and pay wages that dramatically improve over outside options but are meagre by the standards of natives. As such they do dramatically more per capita to reduce global inequality than do the 'fortress welfare states' of the Organisation for Economic Cooperation and Development (OECD) countries. If OECD countries were to imitate the GCC it would reduce global inequality by more than full equalisation within the OE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Opposition to immigration in many high-income countries might be attenuated if immigrants were not granted the full range of rights offered to citizens. Weyl (2018) argues for arrangements similar to those found in the Gulf States where large numbers of immigrant workers have many fewer rights than the native population. believes that unrestricted immigration with no discrimination between immigrants and residents is probably not politically feasible, while the current system of admitting some immigrants who are allegedly treated equally but, in fact, are classed as illegal aliens subject to great uncertainty and discrimination is inefficient and inequitable.…”
Section: International Migration and Inequalitymentioning
confidence: 88%
See 1 more Smart Citation
“…Opposition to immigration in many high-income countries might be attenuated if immigrants were not granted the full range of rights offered to citizens. Weyl (2018) argues for arrangements similar to those found in the Gulf States where large numbers of immigrant workers have many fewer rights than the native population. believes that unrestricted immigration with no discrimination between immigrants and residents is probably not politically feasible, while the current system of admitting some immigrants who are allegedly treated equally but, in fact, are classed as illegal aliens subject to great uncertainty and discrimination is inefficient and inequitable.…”
Section: International Migration and Inequalitymentioning
confidence: 88%
“…Temporary guest worker programs might be a way to accomplish this end, although experience suggests that temporary guest workers have a way of becoming more permanent residents (The Economist 2020a). Weyl (2018) argues that high-income countries would do well to emulate the countries of the Gulf Cooperation Council, which admit large numbers of migrant workers from low-income countries who are paid substantially less than natives doing the same kind of work. While this sort of approach seems to run counter to SDG 10 target 10.3 calling for the elimination of discrimination, such policies might help prevent the adoption of even more restrictive immigration policies.…”
Section: International Migration and Inequalitymentioning
confidence: 99%
“…Anti-migrant sentiment also has the potential to damage the region’s historically open migration policies which have had the net effect of benefiting migrants from a wide variety of countries. Indeed, the Arab Gulf states account for some of the highest levels of annual remittances globally (McAuliffe and Khadria 2020), and Weyl (2018) has suggested that migration to the Arab Gulf countries has massively reduced forms of global economic inequality. As a result, the future of migration to the Arab Gulf states has wide-ranging political, social, and economic implications (Clemens 2011).…”
Section: Discussionmentioning
confidence: 99%
“…either internal or external redistribution (Weyl, 2018;Clemens, 2011). If this empirical work is correct, then the harms of closed borders are many orders of magnitude worse than, say, the injustice committed by the KKK throughout its entire history.…”
Section: Magnitude Of the Underlying Issuementioning
confidence: 99%
“…Consider, for instance, the question of reducing racism in the United States versus the question of opening borders worldwide. The economics literature on open borders overwhelmingly says that open borders would dramatically increase world product, would dramatically increase the welfare of the worst off while also improving the welfare of the better off, and would do far more to equalize and increase world incomes than either internal or external redistribution (Weyl, 2018; Clemens, 2011). If this empirical work is correct, then the harms of closed borders are many orders of magnitude worse than, say, the injustice committed by the KKK throughout its entire history.…”
Section: How To Draw the Linementioning
confidence: 99%